2015
DOI: 10.1016/j.prevetmed.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre-breeding reproductive tract scoring as a predictor of long term reproductive performance in beef heifers

Abstract: In a 7-year longitudinal study 292 Bovelder beef cows in a restricted breeding system in South Africa were observed from 1-2 d before their first breeding season, when reproductive tract scoring (RTS, scored from 1 to 5) was performed, until weaning their 5 th calves. The objective was to determine whether pre-breeding RTS in heifers is a valid tool to predict long-term reproductive performance. Outcomes measured were failure to show oestrus during the first 24 days of the first 50-day AI season (24-day anoest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The farming system, breed and location have been described previously [5,7,20,[23][24][25]. Farm data collected included the following: birth weight and birth date, parity of dam, sire, bull allocated and first to fourth AI day numbered from the mating start date (MSD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The farming system, breed and location have been described previously [5,7,20,[23][24][25]. Farm data collected included the following: birth weight and birth date, parity of dam, sire, bull allocated and first to fourth AI day numbered from the mating start date (MSD).…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of regression models, BCS was categorised into 2 categories (<6 and ≥6) and RTS into 3 categories (1-2, 3 and 4-5) [30]. Diameter of the largest follicle was used either as a continuous variable or was dichotomized using various cut-offs (7,8,9, 12, 13 and 14 mm). Pelvis area (PA) was calculated as the product of the TD and VD, and rescaled values of PA (RPA) as well as uterus diameter (RUD) were calculated within birth cohort using the following formula:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Holm et al (2015) analyzed data from a Bovelder herd (South African crossbred) composed of 12-15-month-old heifers. Although the age is different from the present study, the authors also concluded that an evaluation of the reproductive tract score is a valid management tool to improve reproductive efficiency over the long term, excluding heifers that probably would not breed or could be born late during their first breeding season, and therefore detrimental to the reproductive performance of the subsequent season.…”
Section: Methodsmentioning
confidence: 99%
“…… Farm management and staff were blinded to RTS (reproductive tract scoring) data throughout the study.53 …”
Section: (C) Describe Whether or Not Individuals Involved In Data Comentioning
confidence: 99%